Identification of the Prognostic Value Among Suppressor Of Cytokine Signaling Family Members in Kidney Renal Clear Cell Carcinoma - Changjiu Li (Frontiers Media S.A., 2021)
Background: Kidney renal clear cell carcinoma (KIRC) has become one of the most prevalent malignancies worldwide and remains a crucial cause of cancer-related morbidity and mortality. Aberrant activation of the JAK/STAT pathway acts as an important role in KIRC. The suppressor of cytokine signaling (SOCS) family members are the key negative regulators of the JAK/STAT pathway. SOCS family members have been verified to act as significant roles in regulating cellular responses to many cytokines and growth factors. However, whether the expression levels of SOCS affect the prognosis of patients with KIRC is still elusive.Methods: We first evaluated the expression of SOCS family genes in KIRC and determined the correlation between SOCS expression and different clinicopathological features. Then, we analyzed the genetic alterations, potential functions, transcription factor targets, and immune infiltration of SOCS family members based on the information available on public databases. Finally, we assessed the prognostic value of differentially expressed SOCS family members.Results: The expression levels of SOCS2, SOCS4, SOCS6, SOCS7, and CISH were downregulated in KIRC, and all SOCS genes were associated with clinicopathological features of patients with KIRC. SOCS family members have been predominantly related to protein binding, signaling adaptor activity, and JAK/STAT cascade. We found that STAT3, STAT6, and IRF1 are the key transcription factors that may be participated in the regulation of SOCS. We also found an association between the expression levels of SOCS and the immune infiltrates of KIRC. Finally, we have illuminated that SOCS1 and SOCS3 are risky genes, whereas SOCS2, SOCS4, SOCS6, SOCS7, and CISH are some of the protective genes for patients with KIRC; based on these, we have created a KIRC prognostic index for predicting the prognosis of patients of KIRC.Conclusion: Our study may contribute to further understanding the functions of SOCS genes in KIRC, which may help clinicians in selecting the appropriate drugs and predicting the outcomes for patients with KIRC.